Wear and corrosion studies of graphite‐aluminum composite reinforced with micro/nano‐TiB2 via spark plasma sintering. Issue 2 (15th February 2019) - Durowoju, M.O.; Sadiku, E.R.; Diouf, S.; Shongwe, M.B.; Makena, I.M.; Ramakokovhu, M.M.; Olubambi, P.A.; Eze, A.A.
Abstract: The demand for lightweight materials in the automobile and aerospace industries has led to various researches on graphite and graphite‐aluminum composites. The aim of this study was to investigate the effect of the addition of micron/nano TiB2 particles on the properties of graphite‐aluminum composite particularly the wear resistance. The powders were sintered at 550 °C and 50 MPa with more attention on the effect of the sintering temperature on densification, microhardness, coefficient of thermal expansion, wear and frictional force. The results show that the addition of nano TiB2 reduces the densification while improving the hardness of Gr−Al composite with the lowest value being 96.0 % of relative density and the highest microhardness of 43.58 HV 0.1. The coefficient of thermal expansion and frictional force of the composite materials increases with increasing TiB2 content and heating rate (100 °C/min–150 °C/min). TiB2 particles enhance the wear resistance of graphite‐aluminum composite. The addition of micro/nanoparticles of TiB2 to graphite‐aluminum composite increases its corrosion rate with improved passivation behavior in 3.5 wt.% NaCl solution. Nevertheless, 5 wt.% nano (100 °C/min) TiB2 additions do not affect the overall corrosion rate. This work has shown that we can take advantage of some of the properties of TiB2 to improve the performance of graphite‐aluminum composite.